Seniori-ikäiset digitaalisen terveydenhoitopalvelu Maisan käyttäjinä - Lindfors, Tiina Anneli (2024)
Digital competence is not possible for everyone. There are many people in our society who do not master digital services and are unable to develop these skills. Aging also brings challenges for many people with skills they had before but after aging for example using a computer or mobile phone is no longer possible as it was before. As people's life expectancy increases, so do also various memory disorders and other diseases that hinder the use of technology. There are people in all age groups who do not have such language skills that it would be possible to install and use the equipment without help. The purpose of this study was to investigate if the healthcare system Apotti’s Maisa customer portal is accessible to seniors, what kind of challenges are associated with its use, and how they manage their healthcare matters if the use of the Maisa customer portal is not possible for them and how they feel about rapidly digitalizing health services. The hypothesis was that seniors have problems with the accessibility of Apotti’s Maisa customer portal. These problems are caused, for example, by lack of digital skills, cognitive impairment or learning difficulties caused by memory disorders. A lot of research has been done on the learning of seniors and their use of digital services, but there is still a lack of research data on how people cope when the use of digital services is not possible.